2020
DOI: 10.21203/rs.3.rs-32335/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Anti-CD6 Monoclonal Antibody (Itolizumab) Reduces Circulating IL-6 in Severe Covid-19 Elderly Patients

Abstract: Background: Since the COVID-19 outbreak an unprecedented challenge for healthcare systems around the world has been placed. In Cuba, the first case of COVID-19 was reported on March 11. Elderly with multiple comorbidities have been the most risky population. Although most patients present a mild to moderate disease, some have developed severe symptoms. One of the possible mechanisms underlying rapid disease progression is a cytokine storm, in which interleukin (IL) -6 seems to be a major mediator. Itolizumabis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
2
9
0
1
Order By: Relevance
“…Two studies on preprint servers are available presently; both are from the same Cuban trial (RPCEC00000311). One study shows that a single dose of itolizumab decreased the serum IL-6 levels after 48 h of administration in 24 moderate to critically ill elderly COVID-19 patients [22]. In another study, the authors concluded that in 19 moderately ill elderly COVID-19 patients, itolizumab treatment was associated with a significantly reduced risk of admission to ICU and a 10 times lower risk of death [23].…”
Section: Clinical Trials Of Itolizumab For the Treatment Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies on preprint servers are available presently; both are from the same Cuban trial (RPCEC00000311). One study shows that a single dose of itolizumab decreased the serum IL-6 levels after 48 h of administration in 24 moderate to critically ill elderly COVID-19 patients [22]. In another study, the authors concluded that in 19 moderately ill elderly COVID-19 patients, itolizumab treatment was associated with a significantly reduced risk of admission to ICU and a 10 times lower risk of death [23].…”
Section: Clinical Trials Of Itolizumab For the Treatment Of Covid-19mentioning
confidence: 99%
“…The potential utility of itolizumab in COVID-19, based on its mechanism of action, led to expanded access use and conduct of a trial in Cuba, retrospectively registered with the Cuban regulatory agency (Center for the State Control of Medicines, Equipment and Medical Devices, CECMED) in May 2020. This trial recruited patients with critical and severe illness, and moderately ill patients with very high risk of developing severe symptoms [6]. Encouraged by the initial promising results with the first few patients seen in this index trial, regulatory permission was received to repurpose the drug for COVID-19 in India.…”
Section: Introductionmentioning
confidence: 99%
“…Second, patients with COVID-19 were treated with immunotherapeutics developed in Cuba, including human recombinant interferon alfa-2b 41 , later combined with interferon-γ, a humanized recombinant monoclonal antibody to CD6 (reF. 42 ) and an immunomodulatory peptide, CIGB-258, which is derived from heat shock protein 60 (HSP60) 43 . Third, preventive strategies were introduced for vulnerable populations that used Cuban products to stimulate trained immunity or immunocompetence (Biomodulin T) 40 .…”
Section: Cuban Society For Immunology and Latin American And Caribbeanmentioning
confidence: 99%
“…It could be an attractive therapeutic option to control the cytokine storm in patients with COVID19. 74 Itolizumab is under phase II clinical study in India for the management of moderate to severe ARDS in patients with COVID-19 disease (CTRI Identifier: CTRI/2020/05/024959). 75…”
Section: O Ther D Rugs R mentioning
confidence: 99%